The Mnemonic of Intuitive Ontology Violation is Not the Distinctiveness Effect: Evidence From a Broad Age Spectrum of Persons in the uk and China During a Free-Recall Task - Gregory, Justin P. (Journal of cognition and culture, 2017)
The typical formulation of Pascal Boyer’s counterintuitiveness theory asserts that concepts violating intuitive ontological-category structures are more memorable. However, Boyer’s (2001) original claim centered on the transmission advantages of counter-ontological representations that were cultural. Nevertheless, subsequent studies focused on the recall of novel counterintuitive representations, and an “alternative account” of the memorability of counterintuitive concepts has emerged resembling the distinctiveness effect (Upal, 2010). Yet, experimental evidence shows that familiar concepts have memorability advantages over novel ones (Anaki & Bentin, 2009; Ingram, Mickes, & Wixted, 2011). This investigation of these pan-cultural transmission biases used a large age-representative sample (13–86 years; N = 365) in the uk and China. Results were analyzed by hlm, with familiarity, counterintuitiveness, and delay as 2-level fixed factors, and age as a covariate. No support was revealed for the typical formulation of the hypothesis — however, a significant age effect and interaction of familiarity x counterintuitiveness were found.